Toxicity of soursop extracts to diamondback moth (Bioscience Journal, 2017)
This study aimed to evaluate the effects of three solvent extractors (water, ethanol and hexane) of grounded seeds of soursop, Annona muricata L. (Annonaceae), in the mortality, biology and oviposition of Plutella xylostella L. (Lepidoptera: Plutellidae). The results showed that the LC50 and LC99 were 0.0133 and 0.084%, 0.025% and 0.196%, 2.33 and 35.22% for the ethanolic, hexanic and aqueous extracts, respectively. The organic extracts affected only the larval phase and reduced viability in more than 60%, but did not affect pupal stage of the remaining larvae. Furthermore, the ethanolic extract at lethal concentration also affected negatively the embryonic phase. The results lead to the conclusion that the ethanolic extract of soursop grounded seeds is a viable alternative to control diamondback moth on vegetables.